ANALISIS MODEL STUDENT TEAMS ACHIEVEMENT DIVISION DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA SEKOLAH DASAR - Yasinkawati Putri Bahagia; Nina Nurhasanah; Arifin Maksum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to examine the use of the Student Teams Achievement Division model in improving Civics learning outcomes for elementary school students. This study uses a literature review method by collecting several previous studies to answer the Student Teams Achievement Division model in improving Civics learning outcomes for elementary school students. The data used in this study were obtained through scientific articles taken from the SINTA and Google Scholar databases. Based on the results of this analysis, it can be concluded that the use of the Student Teams Achievement Division model can improve Civics learning outcomes for elementary school students by exposing journal content analysis by analyzing subjects, research objectives, research methods/designs, data collection techniques, data analysis techniques, and results study.